Solid particle erosion protection for the BLOODHOUND SSC front wheel arches - Ben Evans (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
BLOODHOUND SSC is a World Land Speed Record Vehicle designed to travel at speeds of up to 1050 mph (469 m·s−1), with the lower chassis and suspension extremely close to the ground. The shockwave from the nose of the car is expected to fluidise the desert surface of the track in Hakskeen Pan, South Africa. Sacrificial materials must be added to the exterior of the car to limit erosive wear. An open loop gas blast erosion rig was used to test materials at velocities predicted by computational fluid dynamics in the front wheel arches, an area highlighted by the BLOODHOUND SSC engineers as requiring extensive protection. Tests of potential erosion protection materials were performed at 15° and 90° Impact angle using alumina as a substitute for Hakskeen Pan soil. Testing resulted in the use of a 2-mm thick Kevlar 49 laminate and 1.2 mm thick titanium Ti 15 V-3Cr-3Sn-3Al sheet for the wheel arch liner, with titanium Ti 6Al-4V used for the wheel arch lip. The erodent mass flow rate for the application was an unknown variable during testing; the test rig used a specific erodent mass flow rate of approximately 300 kg·m−2·s−1. Depending on in-service erosion rates, the titanium liner may be replaced with either a more durable liner made from Stellite 6B or a less dense liner made from aluminium Al 6082-T6.